Applying CLIL to English language teaching in Thailand: Issues and challenges - Khwanchit Suwannoppharat; Sumalee Chinokul (Universidad de La Sabana, 2015)
Most countries in the world have been influenced by the trends of globalization and interculturality; accordingly, the English language and related cultures have come to play more important roles in global communication. Educational research, a primary source for language teaching and learning development, has increasingly emphasized the importance of integrating language and culture in teaching and learning processes. However, it is not easy for students who use English as a foreign language (EFL) to speak English fluently in an environment where English is rarely used outside the classroom. Teachers nevertheless try to find out the most appropriate teaching approach to develop their students' English skills in order to serve the demands for English in the labor markets. This article discusses the application of CLIL in an EFL context-a case study in Thailand-with an emphasis on explanation of CLIL framework and principles and how these are implemented in Thailand as guidelines for developing EFL courses or curriculum. Both advantages and disadvantages of applying CLIL are examined and the difficulties of applying CLIL in the classroom are clarified to help EFL teachers plan their courses more effectively. Key words: Content and Language Integrated Learning (CLIL), English communication, language teaching and learning, EFL context